Effect of Acacia mangium on broiler performance. - Shanmugavelu, S.; Thayalani, K.; Saminathan, P. M.; M., Marini; S. M., Rosly; M. S., Siti Masidayu; Y., Nor Idayusni; I., Mazwan; H., Zainuddin (2011)
The influence of the supplementation of Acacia mangium on broiler performance was evaluated with a six weeks feeding study. A total of 108 day-old Cobb male broiler chicks were randomly assigned to three corn-soy bean based diets supplementes with 2% Acacia mangium, antibiotics (Salinomycin and Chlortetracycline) or no supplement (Negative Control). The inclusion of Acacia mangium significantly reduced final body weight, average daily feed intake, feed conversion, apparent dry matter digestibility but not average daily feed intake. It was postulated the poor performance of the birds fed Acacia mangium was due to the presence of anti-nutritive components.